Pseudotumor presentation of CMV disease: Diagnostic dilemma and association with immunomodulating therapy. Issue 3 (7th December 2020) - Smibert, Olivia C.; Allison, Cody C.; Doerflinger, Marcel; Pellegrini, Marc; Rischin, Danny; Thai, Alesha; Slavin, Monica A.; Kotton, Camille N.
Abstract: Cytomegalovirus (CMV) is a significant cause of morbidity and mortality in the immunocompromised host. Atypical presentations which include pseudotumors or "cancer mimics" have been described. The etiology of these lesions remains unclear. The authors describe two previously unpublished cases that have arisen in the context of newer immunomodulating therapy and review the existing non‐HIV‐associated CMV pseudotumors described in the literature.